El indio animal en dos novelas de Francisco Leal Quevedo (2013)
ABSTRACT: this article examines the construction of an animalistic image of the Indian in two juvenile novels by Francisco Leal Quevedo: El mordisco de la media noche (2010) and Los hijos del viento: una aventura nukak (2012). The former is set in La Guajira and the latter in the Amazon jungle. It argues that the image of the indigenous animal in these novels is influenced by an anthropological discourse which refers to environmental world views, mediated by the mimetic gesture of fiction itself. The closeness of the Indian to nature comes to be understood as a fusion of both.